Analysis of Risk Factors Malaria Incidence in Indonesia (data analysis of riskesdas 2018) - Apriliani Apriliani; Putra Apriadi Siregar; Azhari Akmal Tarigan (International Archives of Medical Sciences and Public Health, 2021)
Malaria is still a problem in Indonesia and the world because the morbidity rate is still quite high, and its management is a commitment to the Sustainable Development Goals (SDGs) until 2030. The purpose of this study is to determine the risk factors for the incidence of malaria in Indonesia. This study uses a quantitative approach with a cross-sectional study design. Further analysis of Riskesdas 2018 data was carried out from January to August 2021. The location of this research is all provinces in Indonesia, as many as 34 provinces. The sample in this study is the total population based on the Rapid Diagnostic Test (RDT) in Indonesia as many as 26,657 samples. This study uses secondary data from Riskesdas 2018. The data analysis in this study is univariate analysis with descriptive analysis. The results of this study are respondents suffering from malaria aged >24 years as many as 14,769 (55.4%), female respondents suffering from malaria as many as 13,827 (51.9%), respondents having low education suffered from malaria as many as 19,926 (74.7%), respondents working suffered as much as 15,570 ( 58.4%), respondents living in rural areas suffer from malaria as many as 18,558 (69.6%), respondents who sleep without using mosquito nets suffer from malaria as many as 20,671 (77.5%), respondents do not use repellent suffer from malaria as many as 18,104 (67.9%), respondents do not use mosquito coils /spray/electric suffer from malaria as many as 14,059 (52.7%), respondents who do not use mosquito netting on home ventilation suffer from malaria as many as 22,369 (83.9%), and respondents suffer from malaria in Indonesia as many as 8,076 (30.3%). It is hoped that the Indonesian Ministry of Health will monitor the program for using repellents and distributing insecticide-treated mosquito nets to malaria-endemic areas. It is hoped that the District/City Offices should be more effective in providing counselling or education on malaria prevention to the public as a malaria prevention measure.